Cara Menggali Ide-Ide Bisnis Yang Bisa Diterapkan Pada Masa Pandemi Covid-19 - Nico Lukito; Dorina Widowati; Masfar Gazali (Universitas Pahlawan Tuanku Tambusai, 2022)
The Covid-19 Pandemic period greatly affected the income of Micro, Small and Medium Enterprises (MSMEs) and the decline in economic growth had an impact on the sluggish growth of new business establishments. The Bina Amanah Cordova Entrepreneurship School (SKBAC), is an institution that provides entrepreneurship education and training, for example: stalls, workshops, tailors, food vendors, salons, embroidery etc. The purpose of this activity is to provide and share information, ideas about business/business opportunities, which are adapted to minimal capital during the Covid-19 Pandemic. The method of service with counseling by providing information and related knowledge about exploring business ideas during the Covid-19 Pandemic for prospective / MSME actors who are students at SKBAC. The results of the service for SKBAC students, namely MSME actors and prospective actors, better understand how to explore business ideas and add product variety and innovation, including how to market products in the conditions of the online Covid-19 Pandemic in carrying out sales. Students begin to be more confident in developing their business ideas and marketing with social media